(3eYQaI CfhGY Yde GdMOjK (B( (3hHjGf CUhdg hbhGYOg hEjVGM aQhYg hCMcGeg hcTa CSQGQg hTQM eTcdGJg (B)s - (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s
(3ChdgG (B:s
(3bGd GdTjN YQa HGHf GdUdGM GdMeO ddg GdgGOi ef ESJgOGg gPG hEf Yde GdMOjK ef CaVd GdYdhe GdaGVdI hgPg agQSI CfhGYgg aGdChd efgG eYQaI GdUMjM ef GdMOjK hGdKGfi eYQaI GdMSf efg s
(3BNQgG (B:s
(3hai GdMOjK GdKGfi CfS Ohfg Edi CHj eSde hYHO GdQMef Hf HTQ aTjNfG hef HjfgeG CLeYhf fjSGHhQjhf hddg SHMGfg GdMeO hgh MSHfG hfYe Gdhcjd fLR cJGH eYQaI CfhGY Ydhe GdMOjK s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs